Mouse cerebellar granule neurons arrest the proliferation of human and rodent astrocytoma cells in vitro - Hatten, ME (J Neurosci, 1988)
To understand the control of glial tumor cell proliferation, we have examined the effects of neurons on a number of human and rodent glioma lines. These included C6, G26–24, U-251, HTB-16, and A-172 cells of astroglial lineage and G26–20 of bipotential astrocytic and oligodendrocytic lineage. Rapid, specific binding of granule neurons to the human A-172, HTB-16, and U-251 and mouse G26–24 cell lines occurred, after which 3H-thymidine incorporation by these astrocytoma cells dropped 2–5-fold within 12 hr. The number of glial cells remained constant for 5–7 d when the glia were cocultured with granule neurons. Thereafter many neurons detached from the glial cells and glial proliferation commenced again. No effects on glial cell number were seen when PC12 cells were substituted for cerebellar granule neurons. To test the mechanism of neuronal control of glioma cell growth, we added granule neurons or PC12 cells that had been fixed lightly with paraformaldehyde, a plasma membrane fraction of purified granule cells, PC12 cells or astrocytoma cells, or medium conditioned by either granule cells or a mixed population of cerebellar neurons and astroglia. The proliferation of responsive glioma cell lines ceased in the presence of either fixed granule neurons or plasma membranes purified from granule neurons. The addition of fixed PC12 cells or plasma membranes purified from PC12 cells, 3T3 cells, or astrocytoma cells had no effect on glial cell growth.